A forma recombinante da proteína 21 de Trypanosoma cruzi interage com o receptor CXCR4 e diminui a invasão e proliferação de células tumorais de mama humanas - Borges, Bruna Cristina (2019)
Several studies have demonstrated the action of various types of microorganisms and individual components in reduction of tumors in animal models, as well as cultured cells, Trypanosoma cruzi is one of these microorganisms. Parasite’s protein 21 plays a different biological hole directly involved in cell invasion. The recombinant P21 (rP21) binds to macrophages CXCR4 chemokine receptor and has chemotactic activity in immune cells, inhibits angiogenesis and downregulate parasite replication. The aim of this study was verify rP21 effect on non-tumor cells (MCF-10A) and metastatic tumor cells (MDA-MB-231) CXCR4 receptor. Initially, cytotoxicity assay was performed with different concentrations of rP21 in 72 hours of treatment, protein was not cytotoxic in both cells. After cytotoxicity assay, expression of CXCR4 in cell lines, ability of rP21 binds to cells and if this binding was mediated by CXCR4, were investigated. Tumor cells expressed more receptor when compared to health cells, although the expression is different between them: rP21 binds to both cells in a short period of treatment, but is only internalized in MDA-MB-231 cells. After cells treatment, rP21 acts decreasing migration, invasion and blocking cell cycle, especially of metastatic tumor cells. In one hand, rP21 binding is made by CXCR4 receptor in health and breast cancer cells. On the other hand, internalization of recombinant protein and receptor desensitization only in MDA-MB-231. In conclusion, rP21 prevents migration, invasion and progression of the cell cycle in breast cancer cells.